Redescription of the ‘older Adelopsis’ species (Coleoptera: Leiodidae: Cholevinae: Ptomaphagini) based on the analysis of type specimens - Gnaspini, Pedro; Peck, Stewart B. (Zootaxa, 2019)
As preparation for a revision of the Neotropical genera Adelopsis Portevin, 1907, Paulipalpina Gnaspini and Peck, 1996, and Parapaulipalpina Gnaspini, 1996, we review and redescribe the earlier named species and code characters of their genitalia. These characters are then used to redefine species groups. We review the following 22 “older” species: Adelopsis ascutellaris (Murray, 1856) (male lectotype here designated); Adelopsis aspera Jeannel, 1936; Adelopsis asperoides Szymczakowski, 1963; Adelopsis azzalii Szymczakowski, 1975 (here raised to specific status—previously as Adelopsis brunnea azzalii); Adelopsis bellator Szymczakowski, 1968; Adelopsis benardi (Portevin, 1923); Adelopsis brasiliensis Jeannel, 1936; Adelopsis brevicollis Szymczakowski, 1975 (here raised to specific status—previously as Adelopsis brunnea brevicollis); Adelopsis bruchi (Pic, 1926) (male lectotype here designated); Adelopsis darwini Jeannel, 1936; Adelopsis grouvellei Jeannel, 1936; Adelopsis heterocera Portevin, 1907 (the type species of Adelopsis, here considered a junior synonym of Adelopsis ruficollis (Portevin, 1903)); Adelopsis insolita Szymczakowski, 1961; Adelopsis luculenta Szymczakowski, 1963; Adelopsis orcina Szymczakowski, 1975 (here raised to specific status—previously as Adelopsis brunnea orcina); Adelopsis ovalis Jeannel, 1936; Adelopsis pteromoria Szymczakowski, 1975 (here raised to specific status—previously as Adelopsis brunnea pteromoria); Adelopsis ruficollis (Portevin, 1903) (male lectotype here designated) (here considered a senior synonym of Adelopsis heterocera Portevin, 1907); Adelopsis triangulifer Szymczakowski, 1961; Parapaulipalpina filicornis (Jeannel, 1936); Paulipalpina dispar (Portevin, 1903) (male lectotype here designated); and Paulipalpina simoni (Portevin, 1903). The status of Adelopsis brunnea Jeannel, 1936 is discussed, and is restricted to a single, nominal subspecies. Specific status is restablished for Adelopsis linaresi Szymczakowski, 1969 (previously as Adelopsis brunnea linaresi). The status of Paulipalpina claudicans (Szymczakowski, 1980) is discussed. To correct published misidentifications in museum collections, we also describe the following nine new species: Adelopsis claudina sp. n., Adelopsis mrazi sp. n., Adelopsis szymczakowskii sp. n., Adelopsis waclawi sp. n., and Paulipalpina jeanneli sp. n. (all from Brazil), Paulipalpina consuelo sp. n. from Peru, Adelopsis portevini sp. n. and Paulipalpina aragua sp. n. from Venezuela, and Paulipalpina coatepec sp. n. from Mexico. Iutururuca Gnaspini, 1993, described as a subgenus of Adelopsis, is here considered a junior synonym of Adelopsis Portevin, 1907, which is defined as having no subgenera.